Hubungan Tingkat Pengetahuan Dengan Pencegahan Penularan Tuberculosis Paru di Balai Kesehatan Paru Masyarakat (BKPM) Purwokerto - Farhan Fawwaz; Amin Susanto; Wilis Sukmaningtyas (Jurnal Sehat Mandiri, 2022)
Pulmonary tuberculosis is a lung disease caused by Mycobacterium tuberculosis which is the third leading cause of death in addition to other heart and lung diseases in Indonesia. Overcoming the high cases of pulmonary TB disease is very important to be applied in order to reduce the incidence of pulmonary TB which can be in the form of treatment. To reduce the incidence of pulmonary tuberculosis, knowledge is very important because it can reduce the risk of transmission of pulmonary tuberculosis. This study aims to determine the relationship between the level of knowledge and the prevention of pulmonary tuberculosis transmission at the Community Lung Health Center (BKPM) Purwokerto. The samples involved in this study were as many as 65 respondents who were taken using purposive sampling technique. This research is a quantitative study with a correlational design. The results of the spearman-rank test show p-value = 0.000, which means that there is a significant relationship between the level of knowledge and the prevention of pulmonary tuberculosis transmission at the Community Lung Health Center (BKPM) Purwokerto and r = 0.453, which means that it has a sufficient correlation.